2012
DOI: 10.4274/jcrpe.680
|View full text |Cite
|
Sign up to set email alerts
|

Normal Bone Turnover in Transient Hyperphosphatasemia

Abstract: Transient hyperphosphatasemia of infancy and early childhood (THI) is characterized by a temporary isolated elevation of serum alkaline phosphatase activity (ALP), predominantly its bone or liver isoform, in either sick or healthy children under 5 years of age. Return to normal ALP levels usually occurs within four months. Spontaneous rise of ALP might concern the physician, especially when treating seriously ill children. However, THI is considered a benign biochemical disorder with no clinical consequences. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
30
1
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 15 publications
3
30
1
4
Order By: Relevance
“…In the present study, we investigated the bone metabolism markers in patient 1 and found that all markers were normal. This is in line with other reports in which bone metabolism markers, such as serum calcium, phosphate, intact parathyroid hormone (PTH) and osteocalcin, were within the normal range during TH . Based on these facts, we did not investigate bone metabolism in the other patients of the present study.…”
Section: Discussionsupporting
confidence: 87%
“…In the present study, we investigated the bone metabolism markers in patient 1 and found that all markers were normal. This is in line with other reports in which bone metabolism markers, such as serum calcium, phosphate, intact parathyroid hormone (PTH) and osteocalcin, were within the normal range during TH . Based on these facts, we did not investigate bone metabolism in the other patients of the present study.…”
Section: Discussionsupporting
confidence: 87%
“…The pathological origin of the ALP fraction detected in TH is unclear, but Kutilek et al recently reported that the increased ALP activity in TH is not likely from the increased bone turnover. 6 Furthermore, the resistance to heat treatment of the ALP isoenzyme fraction of TH is greater than that of a normal bone fraction. 5 Taking this into account, we speculate that the fraction may be of liver origin.…”
mentioning
confidence: 99%
“…Many case reports [4,6,7,8] and retrospective reviews of patient series [2,9,10,11,12] have been published. Few prospective studies with data on the prevalence of TH in healthy children exist.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have used factors in relation to the upper limit of a reference range, e.g. >3 or 5 times the upper limit for adults [8,15]. …”
Section: Introductionmentioning
confidence: 99%